Prevalence and Correlates of Hyperuricemia in Patients with Hypertension: A Cross-Sectional Study from a Tertiary Care Hospital in Pakistan: Hyperuricemia in Patients with Hypertension - Ahad, Abdul; Qadir, Saima; Khan, Shumaila; Khan, Taimour; Khan, Shahab; Khalid, Fawad (Pakistan Journal of Health Sciences, 2025)
The link between Serum Uric Acid (SUA) and hypertension debated among researchers. Objective: To determine the prevalence and correlates of hyperuricemia in patients with hypertension. Methods: This cross-sectional study was conducted at the General Medicine Department, Saidu Teaching Hospital, Swat (October 2023–April 2024), analyzing hypertensive patients aged 30–60 years. SUA was measured via an automated micro lab, with hyperuricemia defined as SUA >7.0 mg/dl (men) and >6.0 mg/dl (women). Chi-square tested categorical data, while Pearson correlation assessed SUA relationships with SBP, DBP, and BMI (p<0.05 significant). Results: In a total 266 patients, 136 (51.1%) were male. The mean age, BMI were 45.41 ± 25.92 years, and 27.28 ± 3.25 kg/m2, respectively. The obesity was noted in 72 (27.1%) patients. Dyslipidemia was found in 42 (15.8%) patients. There were 54 (20.3%) patients who were newly diagnosed cases of hypertension. The mean systolic blood pressure (SBP), diastolic blood pressure (DBP) were 141.76 ± 8.24 mm Hg, and 91.36 ± 8.45 mm Hg, respectively. The mean SUA level was 6.03 ± 1.13 mg/dl, and the frequency of hyperuricemia was noted in 61 (22.9%) patients. Obesity (p=0.033), and known diagnosis of hypertension (p<0.001) were significantly linked with hyperuricemia, Scatter plot revealed positively linear and significant correlation of SBP (r=0.261, p<0.001), and DBP (r=0.319, p<0.001) with SUA levels. The BMI was also found to have positively linear and significant relationship with SUA levels (r=0.122, p=0.047). Conclusion: Hyperuricemia (22.9%) in hypertensive patients correlated with blood pressure and BMI, indicating its role in complications.